The Influence Ofcustomer Satisfaction As A Mediation To Repurchases (Survey On White Coffee Products In Yogyakarta) - Dyah Sugandini, David Bayu Limawan, Wisnalmawati & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Repurchases are purchases made by consumers second, third and so on .Thisresearch aims to: 1. Analyze price that directly affects repurchases, 2. Analysebrand image that directly affects repurchases, 3. price and brand image influenceon repurchases mediated by customer satisfaction. Subjects in this researchareconsumers of white coffee product in Yogyakarta. The sample uses as many as onehundred respondents,data analysis technique uses Structural Equational Model(SEM) with SmartPLS Program. The results of this research prove: 1. price hasinfluenced on repurchases, 2. brand image has influenced on repurchases, 3. priceand brand image have influenced on repurchases mediated by customersatisfaction. The findings of this study may contribute to consumer behaviormodels, onwhite coffee produtcs and Tripple duties of Higher Education.Keywords: price, brand image, satisfaction, repurchases